100 jaar Plantsoendienst : promenades - parken - funktioneel groen - De Herdt, René; Deseyn, Guido; Van den Hole, W. (Gent: MIAT, 1985)
"Tentoonstelling museum A. Vander Haegen : 21 september - 20 october 1985"